2018
DOI: 10.1242/dmm.033332
|View full text |Cite
|
Sign up to set email alerts
|

Arginine and the metabolic regulation of nitric oxide synthesis in cancer

Abstract: Nitric oxide (NO) is a signaling molecule that plays important roles in diverse biological processes and thus its dysregulation is involved in the pathogenesis of various disorders. In cancer, NO has broad and sometimes dichotomous roles; it is involved in cancer initiation and progression, but also restricts cancer proliferation and invasion, and contributes to the anti-tumor immune response. The importance of NO in a range of cellular processes is exemplified by its tight spatial and dosage control at multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 126 publications
0
82
1
8
Order By: Relevance
“…Reduced arginine up-take by inflamed colon may cause amino acid increase in circulation, which would explain a direct correlation between systemic arginine and the severity of endoscopic inflammation observed in this study. Such an explanation is supported by the observation that ADMA and SDMA, competitors for amino acid transporters [10], were independent predictors of systemic arginine, specifically in active UC. Unlike in other studies [21], active CD here was associated with diminished systemic arginine concentrations and, like in other studies [24], no difference in the case of UC was observed.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Reduced arginine up-take by inflamed colon may cause amino acid increase in circulation, which would explain a direct correlation between systemic arginine and the severity of endoscopic inflammation observed in this study. Such an explanation is supported by the observation that ADMA and SDMA, competitors for amino acid transporters [10], were independent predictors of systemic arginine, specifically in active UC. Unlike in other studies [21], active CD here was associated with diminished systemic arginine concentrations and, like in other studies [24], no difference in the case of UC was observed.…”
Section: Discussionmentioning
confidence: 84%
“…PRMT2 was an exception as it was also upregulated in the inflamed small bowel, whereas in the large bowel, it was more markedly overexpressed in quiescent tissue than inflamed derived from UC patients. Concerning the L-arginine/NO pathway, PRMTs act as negative effectors of NO synthesis by increasing the pool of ADMA and SDMA, inhibitors of NOSs, and competitors for arginine transporters [10]. Taking into account accelerated NO synthesis in IBD and its contribution to the disease pathogenesis [7], the up-regulation of PRMTs might be viewed as beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…31). NO can exhibit both anti-and protumor effects, and has been shown to regulate angiogenesis, apoptosis, cell cycle, invasion, and metastasis (32). Polyamines are highly regulated organic cations that are elevated in proliferating tissues including various cancers (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, a marked cytotoxic effect of MET was observed in co-culture systems, which is in agreement with previous in vitro studies, carried out on BT-20 breast cancer cell line (45). In MOs, as well as in other cells especially macrophages, the amino acid L-arginine is also used as a substrate by arginase to produce polyamines (46) that contribute to the tumor progression (47), and by iNOS to produce NO (46), which has antitumor effects at high levels (48). The current study provides evidence that MOs cultured with breast cancer cells exhibited high levels of iNOS, but remain without marked change when treated with MET.…”
Section: Discussionmentioning
confidence: 63%